Bleaching effectiveness, hydrogen peroxide diffusion, and cytotoxicity of a chemically activated bleaching gel - Oliveira Duque, Carla Caroline de [UNESP]; Soares, Diana Gabriela [UNESP]; Basso, Fernanda Goncalves [UNESP]; Hebling, Josimeri [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Springer, 2014)
The objective of this study was to evaluate the bleaching effectiveness, hydrogen peroxide diffusion (H2O2), and cytotoxicity of a bleaching gel with 35 % H2O2 either associated with ferrous sulfate (FeSO4) or not.Enamel/dentin discs adapted to artificial pulp chambers were placed in compartments containing a culture medium (Dulbecco's Modified Eagle's Medium (DMEM)) and distributed into the following groups: G1-no treatment (negative control), G2-10 % carbamide peroxide (one application for 4 h), G3-35 % H2O2 (three applications for 15 min), and G4-35 % H2O2 + 0.004 g FeSO4 (three applications for 15 min). After treatments, the extracts (DMEM + bleaching components that diffused across enamel and dentin) were applied on human dental pulp cells (HDPCs) and odontoblast-like cells (MDPC-23). Cell viability (MTT assay, Kruskal-Wallis and Mann-Whitney, alpha = 5 %), quantification of H2O2 diffusion, and color change of the enamel/dentin discs (Commission Internationale de I'Eclairage L*a*b* system) were assessed (analysis of variance and Tukey's tests, alpha = 5 %).For both cells, a significant reduction in cell viability was observed for G3 and G4 compared with G1 and G2. No statistical difference was observed between G3 and G4. The rate of H2O2 diffusion was significantly higher in G3 compared with that in G2 and G4. The Delta E value for G4 was statistically higher than that of the other groups.Chemical activation of H2O2 by FeSO4 improves the bleaching effectiveness. However, this metal ion has no significant protective effect against pulp cell cytotoxicity.Although the chemical activation of H2O2 by adding FeSO4 to the bleaching agent improved the bleaching effectiveness, this metal ion has no significant protective effect against pulp cell cytotoxicity.
Keywords: Tooth bleaching; Hydrogen peroxide; Iron; Toxicity